(untitled) (Vietnam Journal of Community Medicine, 2026)
Study aims: Description Clinical Features and Treatment Results of Pediatric Peptic Ulcer Disease with Gastrointestinal Hemorrhage at the Pediatrics Center, Bach Mai Hospital. Methods:A descriptive cross-sectional study in 58 children under 16 years of age diagnosed with gastrointestinal bleeding secondary to peptic ulcer disease at the Pediatric Center, Bach Mai Hospital, from October 1, 2024, to September 30, 2025. Results: The study enrolled 58 cases, with males comprising 81% (male-to-female ratio: 4.27:1). The highest prevalence was observed in the age group >10 years (93.1%). The most common clinical manifestations were gastrointestinal symptoms, overt bleeding, and anemia, respectively: epigastric pain (63.8%), melena (55.2%), and pallor of skin and mucous membranes (79.3%). The most frequent bleeding site was the duodenal bulb (79.3%). According to the Forrest classification, Forrest IIc lesions predominated (39.7%). Blood transfusion was administered to 30 patients, 15 patients, with early endoscopy (<24 hours) performed in 70.7% of cases. Helicobacter pylori infection was identified in 44.8% of patients, all of whom received regimen-based eradication therapy. The majority of patients exhibited symptom resolution with treatment duration <10 days. Conclusion: Peptic ulcer disease complicated by gastrointestinal bleeding predominantly affects male children, with the highest incidence in those >10 years of age. The primary reasons for hospital admission were abdominal pain (46.6%) and melena (55.2%). The leading etiology of gastrointestinal bleeding was duodenal bulb ulceration (79.3%). Early detection, prompt diagnosis, and timely intervention mitigate complications associated with gastrointestinal bleeding due to peptic ulcer disease.